Sosialisasi Batas Aman Kecepatan Sepeda Motor pada Siswa SMAN 62, Jakarta - Sidjabat, Sonya; Purba, Okin; Arofat, Osman (Jurnal Abdimas Transportasi & Logistik, 2023)
Throughout 2023, Motorcycles became the highest contributor to accidents. Accidents are caused by the problem of indiscipline of motorists while driving, which begins with the behavior of violation of the order of passing traffic, and most of the victims are motorists who are still of productive age or students. So this community service aims to socialize the safe limit of motorcycle speed in students public high school 62, Jakarta. With the method of lectures, questions and answers, conducting pre and post-test, demonstrations and practice are given in the presentation of materials and pictures. The result of socializing the safe limits of this motorcycle speed was obtained a satisfaction score of 65% with a rating scale both for the facilitator and 65% for the material provided. The participants of the socialization understood the material provided by the speakers, this can be evidenced by the post-test results, which showed an average good score above 90%. Suggestions for future socialization can be organized with a longer duration, additional props and participants get a guide book.